MULTIVARIATE ANALYSIS OF MORPHOLOGICAL TRAITS IN YAM BEAN Pachyrhizus erosus - Agung Karuniawan (Zuriat, 2005)
The objective of this study was to estimate the genetic diversity among yam bean landraces collected from different islands of Indonesia based on morphological traits. Thirty-six selected yam beans accessions from diverse ecological regions of Indonesia and six accessions from South and Central America were examined. Field trials were performed at two locations in Bogor, Indonesia, in a randomized block design with two replications. Genetic diversity between accessions based on morphological traits was determined by multivariate analysis. Time to flowering, first pod development, leaf length, leaf width, and internodes length played essential role in classification of the yam beans. A clear separation among the yam bean accessions collected from Indonesia, i.e., Sumatra landraces and the landraces collected from eastern Indonesia was detected. Furthermore, American accessions are not obviously separated from Indonesian yam bean materials.